1998
DOI: 10.2118/36595-pa
|View full text |Cite
|
Sign up to set email alerts
|

Backflow in Twin-Screw-Type Multiphase Pump

Abstract: Summary The performance of a twin-screw-type multiphase pump was investigated from the viewpoints of backflow in a gap along the twin-screw shafts and of scaleup parameters. Although both the backflow and the scaleup parameters have been recognized as important factors in developing multiphase pumps, they have not yet been clarified. The twin-screw pump was equipped with pressure sensors, set in the multiphase-test facility, and experimented with under various conditions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 5 publications
4
15
1
3
Order By: Relevance
“…The axial force buildup is roughly constant in the case of the single phase and becomes increasingly parabolic with increasing the GVF. This trend is consistent with the previous test [5,13].…”
Section: Experimental Validation Of the Twin-screw Pump Rotordynamic supporting
confidence: 94%
See 1 more Smart Citation
“…The axial force buildup is roughly constant in the case of the single phase and becomes increasingly parabolic with increasing the GVF. This trend is consistent with the previous test [5,13].…”
Section: Experimental Validation Of the Twin-screw Pump Rotordynamic supporting
confidence: 94%
“…He showed that for an initial circumferential velocity of the fluid entering the seal equals half the rotor surface velocity, the circumferential velocity of the fluid along the seal remains constant and generally has markedly less effect on the total leakage than the pressure-driven flow, especially for a short seal (low length over diameter ratio). In the case of twin-screw pump, discounting the coquette flow effect is consistent with the experimental data that show leakage is independent of pump speed [13].…”
Section: Twin-screw Pump Rotordynamic Modelsupporting
confidence: 88%
“…The increase of volumetric efficiency when the gas content is increased at the suction port (see figures 6 and 7), is a phenomenon that has also been documented for twin screw pumps [8,9,10,11,12]. A model proposed for twin screw pumps supposes that internal clearances are always full of liquid, because the phases are separated under the action of centrifugal forces.…”
Section: Two-phase Pumping Behaviormentioning
confidence: 77%
“…Several former investigations [1][2][3][4][5][6][7] showed already, that screw pumps present a promising method to meet the requirements on the pump performance and the reliability onshore and offshore. Nevertheless, there is still a demand on secure simulation tools for extreme operating conditions like very high gas volume fractions up to nearly 100%.…”
Section: Introductionmentioning
confidence: 99%